Flash Spark Plasma Sintering (FSPS) of Pure ZrB2. Issue 8 (10th July 2014) - Grasso, Salvatore; Saunders, Theo; Porwal, Harshit; Cedillos‐Barraza, Omar; Jayaseelan, Daniel Doni; Lee, William E.; Reece, Mike John; Fahrenholtz, W.
<x xml:space="preserve">Abstract</x> Pure ZrB2 powder was Flash sintered in an SPS furnace (FSPS). The samples were densified up to 95.0% in 35 s under an applied pressure of 16 MPa. Compared to Conventional SPS (CSPS), the newly developed FSPS technique resulted in an unprecedented energy and time savings of about 95% and 98% respectively. ZrB2 monoliths obtained by CSPS and FSPS were compared with respect to microstructures, densification behavior, and grain growth. The developed methodology might find application to a wide range of highly conductive ceramics as such refractory borides and carbides.